Continual sets with the Dirichlet properties and products of Hardy spaces - Dovgoshey, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The problem on the simultaneous approximation of functions from the Hardy spaces by continuous functions on the Riemann sphere for a system of disjoint simply connected domains is considered. A criterion for the solvability of this problem is established.